1979
DOI: 10.1007/bf00155701
|View full text |Cite
|
Sign up to set email alerts
|

Short-term temporal variations of X-ray bright points

Abstract: Skylab S-054 data have been used to examine the flux from X-ray bright points with -90 s time resolution. There is evidence of a steady heating input, similar to one reported for active region loops. Also observed are impulsive brightenings of bright points and rapid decays which are consistent with a sudden turn-off of the steady heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…The time scales of these variations were as short as the temporal resolution of the observations (5.5 min). Similar variations were found in X-rays (Nolte et al 1979). More recently, Madjarska et al (2003) using SUMER observations with a temporal resolution of 50 s, have confirmed the presence within a BP of small-scale transient brightenings of the order of minutes.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The time scales of these variations were as short as the temporal resolution of the observations (5.5 min). Similar variations were found in X-rays (Nolte et al 1979). More recently, Madjarska et al (2003) using SUMER observations with a temporal resolution of 50 s, have confirmed the presence within a BP of small-scale transient brightenings of the order of minutes.…”
Section: Introductionsupporting
confidence: 80%
“…They were first observed and studied in soft X-ray rocket images (Vaiana et al 1970;Nolte et al 1979) where they present an average lifetime of ∼8 h (Golub et al 1974). However, they have also been observed in radio (Marsh et al 1980) and EUV (Habbal & Withbroe 1981) where the emission has an average lifetime of ∼20 h (Zhang et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Microflares in XBPs were already studied by many authors. Nolte et al (1979) observed with Skylab S-054 impulsive brightenings ( < ∼ 5 min) in two XBPs with 90 s time resolution data. They suggested that these intensity variations are the signature of episodic heating superimposed upon continuous input of energy.…”
Section: Discussionmentioning
confidence: 96%
“…MicroÑares in XBPs also were studied by many authors. Nolte, Solodyna, & Gerassimenko (1979) and Sheeley & Golub (1979) observed impulsive X-ray brightenings in XBPs. From observation by the soft X-ray telescope (SXT) aboard Y ohkoh, Strong et al (1992) found that XBPs illustrate their intensity variability over a wide variety of timescales from a few minutes to hours, as well as rapid changes in their morphology.…”
Section: Introductionmentioning
confidence: 98%